PROSES AWAL PEMULIHAN HUTAN GAMBUT KELAMPANGAN-KALIMANTAN TENGAH PASCA KEBAKARAN HUTAN DESEMBER 1997 DAN SEPTEMBER 2002 - Herwint Simbolon (BERITA BIOLOGI, 2004)
Two 1-ha (100m by 100m) plots were established at a peat swamp forest of Kelampangan, Central Kalimantan on May 2002. One plot was established at a forest that has been started to regenerate after forest fire December 1997 (PK) and another one at the unburnt natural forest (HAG). Both plots were separated by artificial canal, about 300m away to southwest (HAG) wards and to northeast wards (PK) of the canal. All trees with stem girth at 130cm height of more than 15cm (or about 4.8 cm in diameter) within the plots were enumerated and measured in May 2002 and re-measured again in May 2003. HAG plot was consisted of 3074 tree individuals grouped into 80 species (Fishers'a = 15.02) with total basal areas of 33.19 mTha, dominated by (top five in BA, from higher to lower): Callophyllum canum, Combretocarpus rotundatus, Campnosperma squamatum, Ctenolophon parvifolius and Cratoxylum glaucum. Species with higher number of individual were: C. canum (515 individuals), Cp. squamatum (355), Ct. parvifolius (350), Elaeocarpus petiolatus (183) and Cr. glaucum (125). PK plot consisted of 1158 individuals, 103 species (Fishers'a = 27.3) and total basal areas were 7.43 mVha, dominated by: Co. rotundatus, Cratoxylum arborescens, Palaquium gutta, Shorea teysmaniana and Syzygium ochneocarpum. Species with higher number of individuals were C. arborescens (256 individuals), S. teysmaniana (104), Sy.ochneocarpum (50), Horsjieldia crassifolia (47) and Cp. squamatum (46). Based on its tree diameter and growth rate, most of the trees (1102 individuals) within PK plot were grown after forest fire December 1997, while the rest 56 trees with higher stem diameter were escaped from forest fire December 1997, mostly belong to: C. canum, Co. rotundatus, Dyera lowii, P. gutta. Based on the species number and total basal areas, the recovery rate of peat swamp forest at PK plot after first forest fire December 1997 were categorized as very high. In September 2002, PK plot was burnt again while HAG remain unburnt, and in May 2003, only 2 individuals of Dyera lowii were found to produce new leaves after escaped from the fire, one laid stem of Co.rotundatus produced new shoot and one standing dead tree of Cr. arborescens produced sprouts from the base of the stem. Growth rate relative,mortality rate and recruitment rate of trees at natural un-burnt forest of the HAG plot were also discussed.